NUMERICAL ANALYSIS OF PORE WATER PRESSURE, SEEPAGE, AND SLOPE STABILITY DURING MENINTING DAM PRE-IMPOUNDING - Jiden Desta Mahendro; Andi Patriadi; Esti Wulandari (jfpublisher, 2026)
Meninting Dam in West Lombok represents strategic hydraulic infrastructure requiring comprehensive evaluation of pore water pressure, seepage behavior, and slope stability during the initial impoundment phase. This study evaluates the dam's hydraulic and geotechnical response through numerical simulation using SEEP/W and SLOPE/W software, validated against field instrumentation data. Numerical modeling demonstrates that reservoir elevation increase from 168.50 m to 196.06 m induces elevated pore water pressure within the core zone, with a maximum value of 505.55 kPa recorded at monitoring instrument Pe.3. Concurrently, seepage discharge escalates from a range of 0.00378 to 0.0133 m³/s during initial filling to 0.0637 m³/s at near-normal water level. These hydraulic responses remain within acceptable operational parameters for earthfill dam structures. Slope stability analysis yields safety factors ranging from 2.052 to 2.860, substantially exceeding the minimum regulatory threshold of FS ≥ 1.5 and confirming structural stability under normal operational conditions. The findings recommend enhancement of the instrumentation monitoring protocol and establishment of an early warning system to improve detection capabilities for pore water pressure fluctuations, seepage anomalies, and potential slope instability mechanisms.